Prediction of drag coefficient of a hybrid body design of aircraft - Shreya Viswanath; Riya Vasan; Venkatachalam Gopalan; Nilesh Satonkar (Mechanics and Advanced Technologies)
This study presents a design of a quintessential hybrid body aircraft, a blended NACA 4414 airfoil winged body. The Design of Elements approach, via Response Surface Methodology (RSM), is used to evaluate the influence of frontal area, chamber angle and materials on the drag coefficient. The Analysis of Variance (ANOVA) is carried out to find the influences of the same. In order to minimize the simulations, a model in RSM, Central Composite Design (CCD) is used. The results of the same are verified via Computational Fluid Dynamics (CFD) simulations. Moreover, combinations of shape memory polymers with composites and graphene nano powder are proposed, for light-weighting and enhanced mechanical properties. A comparison of said materials with commercially used aluminum alloys is done. It is found that the lowest drag coefficient is achievable at a frontal area of 1625 m2 with an angle of attack of -10o and with a material combination of carbon fiber reinforced polymer, glass fiber reinforced polymer, and 10% graphene nano powder by weight.